2021
DOI: 10.1177/00220221211051024
|View full text |Cite
|
Sign up to set email alerts
|

Collective Psychological Ownership and Territorial Compensation in Australia and South Africa

Abstract: Collective psychological ownership as a sense that a territory belongs to a group might explain attitudes of the White majority toward territorial compensation for Indigenous Peoples in settler societies. Ownership can be inferred from different general principles and we considered three key principles: autochthony (entitlements from first arrival), investment (entitlements from working the land), and formation (primacy of the territory in forming the collective identity). In two studies, among White Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Ownership principles are reasons that can be used to argue for group ownership, such as the principle of having been first or having invested into the land ( Verkuyten and Martinović, 2017 ). While having been first is a rather exclusive ownership argument—only one group can have been the first—having invested into the land can be more inclusive—two groups could have invested together—and could thus relate to stronger perceptions that a relevant outgroup also owns the territory ( Nooitgedagt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ownership principles are reasons that can be used to argue for group ownership, such as the principle of having been first or having invested into the land ( Verkuyten and Martinović, 2017 ). While having been first is a rather exclusive ownership argument—only one group can have been the first—having invested into the land can be more inclusive—two groups could have invested together—and could thus relate to stronger perceptions that a relevant outgroup also owns the territory ( Nooitgedagt et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These rights might be granted by supporting conciliatory policies. Research has shown that in settler societies people of White European origin with higher perceptions of indigenous (outgroup) ownership of the land are more willing to offer territorial compensation to indigenous people ( Nooitgedagt et al, 2021 ), thereby extending these groups’ land rights. Similarly, there is support for the idea that outgroup ownership perceptions relate to conciliatory policies among Israeli Jews.…”
Section: Introductionmentioning
confidence: 99%
“…This is referred to as collective psychological ownership (Pierce & Jussila, 2011), such as ownership of territories like “our beach” (Due & Riggs, 2008), “our neighborhood” (Toruńczyk‐Ruiz & Martinović, 2020), and “our land” (Nijs, Martinović, Verkuyten et al, 2021). Importantly, people not only have a sense of what belongs to their ingroup, but can also recognize outgroups as owners (Nooitgedagt, Martinović et al, 2021; Storz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In settler societies, however, settlers are likely to recognize that Indigenous Peoples arrived first, while they may simultaneously believe that their ingroup has invested more. Research in Australia and South Africa has shown that Whites' support for the autochthony principle was related to perceiving more indigenous ownership, while support for the investment principle was related to perceiving more nonindigenous ownership (Nooitgedagt, Martinović et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…adapted from previous research on collective psychological ownership in relation to territories (Nooitgedagt, Martinović, Verkuyten, & Maseko, 2021;Storz et al, 2020). The first set of items referred to the 'ingroup' (European New Zealanders), and the second to the Indigenous 'outgroup' (Māori) (ρ = .83; .85, respectively).…”
Section: Methodsmentioning
confidence: 99%